(untitled) (Foro de Educacion, 2016)
Citizenship is a complex and important issue in education. The focus of our work is on learning citizenship rather than on citizenship education, because we believe it is necessary to start from an understanding of what citizenship is, how it is exercised and how it is learned. In this paper we address the process followed in two research projects on learning of citizenship and participation, emphasizing the qualitative and participatory methodology and some of the results: those related to the meanings of the concept «citizenship» itself, which represent such a dynamic characterization of this term that it is required to refer to it in plural; and to the experiences and scenarios in which we learn, that deal with practices, relationships and diversity of those involved in any space. The research process has led us to reconsider conceptual and methodological aspects to introduce participation as a central component in the research process. The lessons drawn from the research projects are highlighted as conclusions in the article, refer to aspects such as the enrichment of research, the development of researchers’ skills or the flexibility with which we must approach the research process.